«The Poetry and Music of Joaquín Sabina. An Angel with Black Wings», de Daniel J. Nappo (Castilla. Estudios de Literatura, 2022)
Reseña del libro The Poetry and Music of Joaquín Sabina. An Angel with Black Wings (Londres, Lexington Books, 2021), de Daniel J. Nappo.